Nutritional Status and Obesity Prevalence in People with Gender Dysphoria - María Victorina Aguilar Vilas; Gabriela Rubalcava; Antonio Becerra; María Carmen Martínez Para (AIMS Press, 2014)
Gender dysphoria is a condition that involves a failure to adapt and a body dissatisfaction that makes these individuals especially susceptible to eating disorders. The aim of this paper was to ascertain the nutritional status, dietary behaviour and lifestyle and their effect on overweight/obesity prevalence of the people with gender dysphoria.Methods: A longitudinal study on 157 individuals from the Gender Disorder Unit at the Ramón y Cajal Hospital (Madrid) who are undergoing hormonal treatment has been carried out. Usual dietary intake, physical activity habits and socioeconomic parameters were evaluated. The anthropometric parameters determined were weight, height, body-mass index (BMI), waist and hip circumference and body fat content. Results: The mean of the population eats a large number of servings of food, which leads to high levels of energy intake: 3,614.32 ± 1,314 kcal/day. These intakes are related to the physical activity performed. The average diet among this population is unbalanced, with a high consumption of fats, especially saturated fats and cholesterol. The breakfast is skipped by 16% of the population. Together with cross-hormone treatment, this dietary habitsand lifestylelead to an increase in body fat, especially in the female to male group whose overweight andobesity prevalence increase (22.72% vs 34.85%). Conclusion: This population suffers a change of their nutritional status due to a variation in their eating behaviour and lifestyle. This increase in the obesity prevalencemake it susceptible to chronic diseases and cardiovascular disorders. It is therefore necessary to include nutrition education courses in the comprehensive treatment programme (anatomical, psychological, etc.) for these individuals.